Energy Optimization of Building in Revit with Passive Design Strategies for Kathmandu, Nepal - Rai, Aishra Krish (International Journal on Engineering Technology, 2026)
The building sector is a major contributor to global energy consumption. Innovations aimed at reducing energy use in this sector can significantly advance the achievement of Sustainable Development Goals. Climate-responsive buildings leverage natural climatic elements, such as air temperature, relative humidity, wind, solar irradiation, and rainfall to minimize energy demand for heating, cooling, and lighting. This study optimized building strategies for the warm-temperate climate of Kathmandu, Nepal, using Autodesk Revit. The result obtained from building energy simulation of the baseline and passive building showed significant reduction in Energy Use Intensity and Heating, Cooling, Lighting and Equipment load. The building optimized with passive design strategies consumed 21% less energy and performed 22% better in total site energy reduction and Energy Use Intensity Reduction compared to the normal building, demonstrating the effectiveness of climate-adaptive design in reducing operational energy demand. These findings contribute to the achievement of SDG 7 (Affordable and Clean Energy), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 13 (Climate Action).